Formulasi dan Uji Mutu Fisik Sediaan Sabun Cair Ekstrak Biji Mahoni (Swietenia mahagoni L) - masfah raudlotus (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2023)
Abstrack The skin is a place of excretiom, the result of the excretion is in the form of sweat that has been mixed with bacteria that can cause infection, so preparations from natural ingredients that contain antibacterial are needed. Mahogany seeds (Swietenia mahagoni L) contain alkaloids, flavonoids and saponins with the ability to inhibit antibacterial and antimicrobial inhibition. This study aims to formulate liquid soap preparations mahogany seed extract with a concentration of 0%, 20% and 50% by testing the physical quality of liquid soap preparations in the form of pH test, organoleptic test, homogeneity test, high foam test, free alkali test and stability test. The results of the evaluation of the physical quality test of liquid soap preparations with concentrations of 0%, 20% and 50% showed that the three formulations did not experience organoleptic changes, homogeneity and stability. The foam height test has a range of 111-128 mm, the pH test has a range of 8.91-9.69 and the free alkali test shows a pink color. The conclusion of this study is that liquid soap with mahagony seed extract (Swietenia mahagoni L) meets the requirements in accordancewith the requirements set by SNI 06-4085-1996.